Clinicopathological and prognostic significance of heat shock protein 27 (HSP27) expression in non-small cell lung cancer: a systematic review and meta-analysis - Li, Shuangjiang (Springerplus, 2016)
Numbers of clinical and experimental investigations have provided increasing evidences to demonstrate that heat shock protein 27 (HSP27) is a qualified predictor for many cancers. However, no consensus has been reached on its clinicopathological and prognostic significance in patients with non-small cell lung cancer (NSCLC). Therefore, we performed this systematic meta-analysis to help addressing this issue. PubMed, EMBASE, the Web of Science and China National Knowledge Infrastructure were searched for full-text literatures met out eligibility criteria. We determined the odds ratio (OR) and hazard ratio (HR) as the appropriate summarized statistics for assessments of clinicopathological and prognostic roles of HSP27, respectively. Q-test and I(2)-statistic were used to evaluate the level of heterogeneity. Sensitivity analysis was conducted to examine the stability of overall estimates. Potential publication bias was detected by Begg’s test and Egger’s test. Finally, ten articles were identified to be included into our meta-analysis. The pooled analyses suggested that HSP27 expression was significantly associated with the unfavorable conditions for differentiation degree, lymphatic metastasis, clinical stage, squamous cell carcinoma and tumor size. However, HSP27 expression had no significant relationship to gender, age and smoking status. Meanwhile, pooled HRs indicated that HSP27 expression could be a predictor for a lower 5-year overall survival (OS) rate (HR: 1.832; 95 % CI 1.322–2.538; P < 0.001) but not for 1-year OS of NSCLC (HR: 0.885; 95 % CI 0.140–5.599; P = 0.896). In conclusion, our meta-analysis demonstrates that HSP27 expression may be a strong biomarker to predict both the poor clinicopathological and prognostic characteristics in patients with NSCLC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-016-2827-8) contains supplementary material, which is available to authorized users.